Early Visual Functional Outcomes and Morphological Responses to Anti-Vascular Growth Factor Therapy in Diabetic Macular Oedema Using Optical Coherence Tomography Angiography - Dabir S (Dove Medical Press, 2021)
Supriya Dabir,1 Mohan Rajan,1 Liji Parasseril,1 Vaidehi Bhatt,2 Preetam Samant,3 CAB Webers,4 TTJM Berendschot4 1Department of Retina, Rajan Eye Care Pvt Ltd, Chennai, India; 2Rajiv Gandhi Medical College, Thane, India; 3Department of Retina, PD Hinduja Hospital and Medical Research Center, Mumbai, India; 4University Eye Clinic, Maastricht, the NetherlandsCorrespondence: Supriya DabirRajan Eye Care Hospital Pvt. Ltd, No. 5, Vidyodaya East 2nd Street, T. Nagar, Chennai, Tamil Nadu 600017, IndiaTel +919900974800Email supriad@gmail.comPurpose: Diabetic macular oedema (DME) is a vision-threatening complication of diabetic retinopathy. Spectral domain optical coherence tomography angiography (OCTA) is useful for assessing DME. We performed serial OCTA measurements before and after 3 monthly intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections to understand its relationship with best corrected visual acuity (BCVA), central macular thickness (CMT) and vascular indices.Methods: OCTA assessment consisting of 6 × 6 mm scans centred on fovea and en-face retinal angiograms were obtained. Scans were done at baseline and at 1 month following each of the 3 intravitreal injections of anti-VEGF (ranibizumab, Lucentis®).Results: Our prospective study included 24 eyes of 24 subjects, aged 63.0 ± 5.0 years. There was a mean gain of 0.07 LogMAR (3 letters) and reduction of CMT, vessel density (VD) and perfusion density (PD) by end of 3rd month. CMT was independently associated with improvement in BCVA. There were significant reductions in FAZ area, VD and PD over 3 months from baseline.Conclusion: At three months, intravitreal anti-VEGF therapy is associated with visual function recovery in DME, with reduction in CMT being the most reliable predictor of response. OCTA shows a reduction in VD and PD respectively suggestive of reduced macular perfusion in the short term. Simultaneous reduction in FAZ size can be due to reversal of manual displacement of the retinal capillaries resulting from resolution of intraretinal oedema.Keywords: diabetic macular oedema, superficial capillary plexus, vascular density, perfusion density, foveal avascular zone, optical coherence tomography angiography, macular ischemia